Diagnosis of temporomandibular joint disorders: indication of imaging exams - Ferreira,Luciano Ambrosio (2016)
ABSTRACT INTRODUCTION: Knowledge of the different imaging tests and their appropriate indications is crucial to establish the diagnosis of temporomandibular disorders, especially in patients with overlapping signs and symptoms. OBJECTIVE: To present and assess the main diagnostic imaging tests for temporomandibular disorders and rationally discuss their indication criteria, advantages, and disadvantages. METHODS: Literature review in the Web of Knowledge, PubMed and SciELO databases, as well as manual search for relevant publications in reference lists of the selected articles. RESULTS: Computed tomography and magnetic resonance imaging were considered the gold standard assessments for the temporomandibular joint to evaluate hard and soft tissues, respectively. Each diagnostic method exhibited distinct sensitivity and specificity for the different subtypes of joint dysfunction. CONCLUSION: Selecting an evaluation examination based on its accuracy, safety, and clinical relevance is a rational decision that can help lead to an accurate diagnosis and an optimum treatment plan.